IMPROVING THE QUALITY OF LEATHER SHOES USING SIX SIGMA AND KAIZEN METHODS (Science and Technology (SciTech), 2022)
UD PAS Clasik is a company that produces shoes from genuine cow leather. The problem that exists is that there are still many defective products by 22.31% of the total production of 910 units. The condition of the production site is dirty and untidy. This study aims to determine the types of defects and the factors that cause defects, then propose product quality control using the six sigma and kaizen methods. This study uses the six sigma method with DMAIC analysis (Define, Measure, Analyze, Improve, Control) and kaizen in the form of Five-M Checklist and Kaizen Five-Step Plan as well as the implementation of visual management at the improve stage. The results of processing the average DPMO value of 227018, and the average sigma level of 2.25. The highest type of defect was glue stains at 62.56% of the total defects of 127 units. From the results of the analysis of the fishbone diagram and the Five M Checklist, there are five factors that cause the problem, namely humans, methods, machines, raw materials and the environment. While the Five Step Plan with 5S steps (seiri, seisi, seiton, seiketsu, and shitsuke) and the application of visual management. The DPMO value decreased by 112434,7 and the sigma value increased by 0.45. By decreasing the DPMO value and increasing the sigma value from 2.25 to 2.70, it indicates that the implementation is quite successful because it is able to reduce the number of product defects